Achievement goal orientation and cohesivity reduce social loafing tendency among undergraduate students - Purna, Rozi Sastra; Sari, Liliyana; Angraini, Fitri; Armalita, Rani; Oktari, Siska (International Journal of Research in Counseling and Education, 2022)
Working in a group setting is commonly implemented in higher education as part of student-centered learning. However, the social loafing phenomenon has been reported to disrupt the performance of university students in group assignments. The current study aims to examine the influence of achievement goal orientation and cohesivity on social loafing among undergraduate students. A total of 377 undergraduate students (70.8% females) in Indonesia was recruited through cluster random sampling. All respondents answered three questionnaires, namely Social Loafing, Achievement Goal Orientation, and Cohesivity Scales. Partial Least Squares Path Modeling (PLS-PM) was used to analyze the correlations among variables that were built into the research model. The results showed that both achievement goal orientation and cohesivity had a significant negative effect on social loafing. In addition, cohesivity was reported to partially mediate the effect of achievement goal orientation on social loafing. It was also revealed that the research model was a fairly high model fit to explain the relations among variables in the study. These findings suggest that both achievement goal orientation and group cohesivity could reduce social loafing tendency during group tasks among university students.